Bulgarians in the Mont Athos Until the End of the 14th Century - Чешмеджиев, Димо (Poznańskie Studia Slawistyczne, 2016)
n the present work, we review the question of the presence of Bulgarians in the Mont Athos region during the the middle ages. We then examine the topic of the first orthodox monastery there and the main steps in the establishment of relations of the Bulgarian lands and state with the monastic republic.